Comparison of serum levels of interleukin 33 in combination with serum levels of C-reactive protein, Immunoglobulin G, Immunoglobulin A, and Immunoglobulin M in recurrent pregnancy loss: A case-control study - Hossein Ali Khazaei; Farahnaz Farzaneh; Saeedeh Sarhadi; Javid Dehghan Haghighi; Forough Forghani; Vahid Sheikhi; Bahman Khazaei; Lida Asadollahi (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: One of the critical cases of recurrent pregnancy loss is immunological factors, whereas obtaining effective prevention or treatment is necessary for cognition of reasons. Objective: In this study, we tried to evaluate some immunological factors related to recurrent pregnancy loss. Materials and Methods: This case-control study was conducted on 66 women at the age of 18-35 yr who were referred to the Clinic of Gynecology and Obstetrics, Ali Ibn Abi Taleb hospital, Zahedan, Iran, from August-December 2019. Interleukin 33 (IL-33) serum levels were measured using enzyme-linked immunosorbent assay. Immunoglobulin G, Immunoglobulin A, Immunoglobulin M (IgM), and C-reactive protein levels were measured by serology and hematology methods. Results: The mean age of total participants was 30.8 ± 3.80 yr. The mean serum IL-33 in the case group was 318.5 ± 254.1 pg/ml and was lower than the control group (354.2 ± 259.9 pg/ml), which was not statistically significant (p = 0.52). The level of C-reactive protein in the case and control was not significantly different (p = 0.27), and Immunoglobulin A and Immunoglobulin G in the case and control were also not significantly different (p = 0.46, and p = 0.16, respectively), but there were significant differences (p = 0.003) between the level of the IgM in the case and control groups. Conclusion: No statistically significant difference was observed in the IL-33 serum level, for at least 4-6 months after the last abortion in the case group and the final live birth in the control group. In contrast, serum levels of IgM were statistically significant. Finally, the need for more studies is felt according to the different results of the previous studies in this field.